37 Safety in seconds 2.0: a smartphone app to improve child passenger safety behaviours. (19th September 2017) - Omaki, Elise; McDonald, Eileen; Shields, Wendy; Aitken, Mary; Bishai, David; Rizzutti, Nicholas; Stevens, MW
Abstract : Purpose: Although child safety seats are known to reduce the risk of death from motor vehicle crashes, use among children 4–7 years old remains low and misuse is widespread. The aim of this prospective randomised trial was to test the efficacy of a smartphone app, Safety In Seconds 2.0, which delivered theory-based tailored education about child safety seats to parents in Little Rock, Arkansas and Baltimore, Maryland Methods: Parents of children aged 4–7 visiting the paediatric emergency room in the two participating sites (regardless of the reason for the visit) were recruited. Study participants downloaded the Safety In Seconds app onto their smartphone and were randomised to the intervention (car seat) or control (fire safety) group. Both groups completed a 10 min assessment about their safety knowledge and behaviours and received tailored feedback relevant to their study group. The app contained a portal with educational links and sent monthly push notification reminders for parents to interact with the app. Parents completed follow-up assessments at 3 months and 6 months. Results: A total of n=1129 parents were enrolled, and 742 (66%) completed the 6 month follow-up survey. At follow-up relative to the CG, IG parents were more likely to report using the correct child safety seat for their child's age and size (OR=1.8; p<0.01) and were more likely to have had their child's safety seat inspected by a car seat technician (OR=1.4; p<0.05). Conclusions/Significance: Smartphone applications hold potential for changing behaviours that are known to improve child passenger safety.